Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis. Issue 16 (12th August 2021) - Huang, Hung-Tse; Lin, Yu-Chi; Zhang, Li-Jie; Liaw, Chia-Ching; Chen, Hsin-Yen; Hsueh, Ming-Tung; Kuo, Yao-Haur
Abstract: This research isolated two new oleanane-type triterpene glycosides, named mocochinosides A (1 ) and B (2 ), together with ten known compounds as chikusetsusaponin IVa ethyl ester (3 ), momordin Ib (4), momordin IIb (5 ), momordin II (6 ), calenduloside G (7 ), calenduloside H (8 ), elatoside A (9 ), elatoside C (10 ), calendulaglycoside C 6'- O -7-butyl ester (11 ), and hederagenin 3- O - β -D-glucuronopyranoside (12 ) and characterized them from the vines of Momordica cochinchinensis . The new structures of both glycosides 1 -2 were elucidated by spectroscopic analysis including 2 D NMR and MS, followed by an analysis of their anti-inflammatory and cytotoxic activities. Compounds 1, 4, and 11 showed moderate inhibitions for NO production on RAW264.7 macrophages induced by LPS at IC50 5.41 ∼ 11.28 μM. Compounds 3, 4, and 7 (IC50 8.42 ∼ 19.74 μM) exhibited potential anti-proliferative activities against both of WiDr and MCF-7 human tumor cell lines. GRAPHICAL ABSTRACT: